Treatment seeking by employment characteristics among Australian males: a longitudinal study from the Ten to Men study. (December 2018) - Milner, A.; King, T.L.; Scovelle, A.J.; Currier, D.; Spittal, M.J.
Abstract: Objectives: Men are less likely to seek treatment for mental health problems than women; however, the structural employment-related factors influencing this relationship are unknown. Study design: This is a prospective cohort study. Methods: Using the Australian Ten to Men cohort (N = 6447), we examined the relationship between being in a male-dominated occupation and treatment seeking from a mental health professional compared to being in a gender-equal occupation. Models were fit using logistic regression. Results: There was some evidence of a stepwise gradient between male-dominated occupations and treatment seeking for mental health problems. However, results were only significant for the most male-dominated occupations after adjustment (odds ratio [OR] 0.70, 95% confidence interval [CI] 0.52 to 0.94, P = 0.017). We also found evidence that individuals who more strongly adhered to masculine norms had a lower likelihood of treatment seeking (OR = 0.97, 95% CI 0.95 to 0.99, P = 0.004). Conclusions: This supports the idea that occupational-related factors influence male treatment seeking for mental health problems. Highlights: Poor treatment seeking for mental health problems is an identified problem among men. Occupational context and individual gender norms influenced treatment seeking. Men in the most male-dominated occupations had lower odds of treatment seeking.